Application of Pb-Resistant Bacteria to Reduce Pb-Accumulation in Brassica sp. on Pb-Contaminated Soil - Beauty Laras Setia Pertiwi; Yulia Nuraini; Sugeng Prijono; Reni Ustiatik (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Brassica sp. is a horticultural crop with high demand for consumption. To meet the demand, farmers apply intensive farming to increase yields and prevent plant pests and diseases that cause yield loss. Agrochemical applications in the form of inorganic fertilizers and pesticides contribute to lead (Pb) contamination in agricultural soils and increase lead (Pb) content in the cultivated plants. Nowadays, using bacteria for remediation (bioremediation) is environmentally friendly and effective in cleaning pollutants by converting organic Pb into inorganic Pb which is less toxic. This study aims to explore Pb-resistant bacteria that can reduce Pb-accumulation on food crops such as Brassica sp. grown in Pb-contaminated soil. This study isolated 15 isolates that survived on nutrient agar containing 1,000 mg/L Pb(NO3)2. The study showed 2 potential Pb-resistant bacteria that reduced Pb accumulation in Brassica sp. up to 30.5%. The bacteria are gram-positive bacilli and non-human pathogens (PT-3 and PT-5). DNA barcode identification results showed the isolates identified as Bacillus altitudinis (PT-3) and Bacillus wiedmannii (PT-5). Aplication of the bacteria increases the shoot length and fresh weight of Brassica sp. Application of the bacteria improves food crops quality by reducing heavy metals accumulation, such as Pb. Thus, the bacteria are potential as biofertilizers for reducing agrochemicals use in intensive agriculture areas and preventing environmental destruction and food contamination. Keywords:   Bioremediation, Brassica sp., Inorganic Fertilizers, Lead-Resistant Bacteria, Pesticides.